Application of compounding process mathematical model for gasoline quality improving - Dolganov I. M. Igor Mikhailovich; Ivanchina E. D. Emilia Dmitrievna; Dolganova I. O. Irena Olegovna; Solopova A. A. Anastasia Alexandrovna; Seytenova G. Zh. (2016, 2016)
Title screen